(untitled) - Warren,Roxanne (New York, 1997)
Decentralization and the flight to the suburbs have drained the economic and cultural life out of many urban communities, while driving our consumption of land and fuel to new heights. But the option of conventional planning for higher densities raises the specter of concrete landscapes filled with cars. The Urban Oasis would contrast with this image. In this thoughtful and insightful book, architect Roxanne Warren makes a compelling case for the benefits of relatively high-density, but abundantly landscaped, mixed-use, walkable new "development clusters" - as traffic-calmed or pedestrian zones. To allow sufficient land for a green living environment, car parking would be located peripherally, and automated people movers would provide around-the-clock, readily available links to regional transit networks. Whether built on rehabilitated urban land, or threaded through land on former commercial strips, such human-scale communities would combine the sociabilities of urban living with fresh air and greenery, and would aim to resolve many of the intertwined population/congestion/environmental pressures of our time. The book is packed with case studies of existing pedestrian zones in Europe and the U.S. It also contains clear and illuminating descriptions of automated people mover technologies, and in doing so, bridges the gap between humanist and technological concerns.
Keywords: Dity planning,Environmental policy,Greenways,Pedestrian areas,Urban ecology,Urban policy,Urban transportation; United states,United states,United states,United states,United states,United states,United states